Techno-chemical description of starfish as an object of industrial processing - Valery D. Bogdanov; Svetlana N. Maximova; Nickolay G. Tungusov; Ekaterina V. Shadrina (Известия ТИНРО)
Size-weight parameters and chemical composition of starfish from the Severnaya Bay (Peter the Great Bay, Japan Sea) are investigated. Two starfish species: Evasterias echinosoma and Patiria pectinifera form dense aggregations in the bay at aquaculture plantations of Far-Eastern Technical University. Their largest size and weight are observed in spring and summer. The main part of their body weight is presented in any season by coating connective tissue that contains proteins (9.5-14.3 %), lipids (0.7-3.8 %), and mineral substance (1.3-32.0 %). The proteins include all essential amino acids (36.4-39.4 % of total amino acids weight) and the lipids include unsaturated fatty acids (20.7-22.7 % of total lipids weight). Viscera of starfish are distinguished by high content of potassium and iron and the proteins of viscera have heightened content of essential amino acids (on average 40.3 % of total amino acid weight for P. pectinifera and 44.3 % for E. echinosoma ). High biological value of the starfish tissues determines prospects of their use as raw material for industrial processing to functional foodstuffs.